A composite wheel spanner (2011)
A composite wheel spanner that simultaneously unscrews four wheel nuts/bolts of a Golf 4 Volks Wagon comprises the gear box casing (001) an enclosure of multiple gears and shafts that allows transmission of torque from the handle to the wheel bolts. The gears are located in the gear box and are held by shafts having keys and keyways. The gear shaft is an axle of the gear that provides rotation that allows a gear to engage with another gear while in operation. Spanner socket (002) fixed to the gear casing in a radial path are used in loosening the wheel bolts. The Handle (003) drives the gears by applying a whining force. The stand (004) and Base (005) hold together the gear box, the shafts and other elements.